2017
DOI: 10.5455/jice.20170330010555
|View full text |Cite
|
Sign up to set email alerts
|

Documentation of ethnomedicinal information and antimicrobial validation of Thespesia populnea used by Yanadi tribe of Ganugapenta village, Chittoor District, Andhra Pradesh, India

Abstract: Aim:This study aimed to document the traditional knowledge of medicinal plants and antimicrobial validation of Thespesia populnea used by Yanadi tribe of Chittoor district, Andhra Pradesh, India.Materials and Methods:The study was mainly focused on documentation of medicinal plants used by Yanadi tribe to treat different diseases with a standard questionnaire. These plants were cross-checked in Dr. Dukes Database and available literature to know the significance of this tribe on medicinal knowledge. Among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…In Samoa, T. populnea bark is used to treat stomatitis [ 53 ]. In India, T. populnea leaf, fruit and stem bark were cited as anti-inflammatory agents [ 103 ]. Regarding its pharmacological properties, one study showed that T. populnea seeds possess in vivo anti-inflammatory, analgesic, and antipyretic properties [ 104 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Samoa, T. populnea bark is used to treat stomatitis [ 53 ]. In India, T. populnea leaf, fruit and stem bark were cited as anti-inflammatory agents [ 103 ]. Regarding its pharmacological properties, one study showed that T. populnea seeds possess in vivo anti-inflammatory, analgesic, and antipyretic properties [ 104 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is an essential plant for medicinal use with several pharmacological properties. It can be used as an anti-inflammatory, analgesic, antipyretic, antidiarrheal, hepatoprotective, antioxidant, and wound healing, in addition to having antiproliferative activity against cancer (Nirmal et al 2015, Lindamulage & Soysa 2016, Hiteksha & Mamta 2017, Savithramma et al 2017, Rangani et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoid-rich fractions of O. amentacea have also been shown to exhibit potent antioxidant and antidiabetic activity by inhibiting key enzymes such as α-amylase and α-glucosidase related to type II diabetes, which has been considered an effective strategy for controlling blood sugar [13,14] . The bark is used for the treatment of snakebites, fever and the fruits are consumed by the Malayali tribes of Tamil Nadu, India [17] . The plant is also involved in the treatment of malaria [18] liver diseases and in the treatment of sexually transmitted diseases [19] .…”
Section: Introductionmentioning
confidence: 99%